A Tailgut Cyst-Cystic Mass Diagnosed by Prenatal Ultrasonography - Ki Yeong Chung; Na Mi Lee; Eung Sang Choi; Byoung Hoon Yoo; Gwang Jun Kim; Seong Jae Cha; Gi Hyeon Kim; Mi Kyung Kim (Thieme Medical Publishers, Inc., 2013)
Abstract Tailgut cysts are congenital lesions found in the presacral space. These have been mainly identified in adults and are rare in children, especially neonates. Here, we present the case of a neonate with a presacral cystic mass detected by prenatal ultrasonography that was diagnosed as a tailgut cyst after postnatal surgical removal. When a presacral cyst is encountered, tailgut cyst should be considered in the differential diagnosis.